Effects of a cognitive modulator in the theta and alpha asymmetry during a typewriting task: a sensorimotor integration perspective Efeitos de um modulador cognitivo na assimetria de teta e alfa durante uma tarefa de datilografia: uma perspectiva da integração sensório-motora - Marlo Cunha; Sergio Machado; Luiz Cláudio Miana; Dionis Machado; Victor Hugo Bastos; Bruna Velasques; Maurício Cagy; Luis F. Basile; Roberto Piedade; Pedro Ribeiro (Arquivos de Neuro-Psiquiatria)
This study aimed to elucidate cortical mechanisms and to identify the areas where occur such mechanisms due to interaction between bromazepam and motor learning. The sample was composed of 45 healthy subjects randomly distributed in 3 groups: placebo (n=15), bromazepam 3 mg (n=15) or bromazepam 6 mg (n=15). To perform the experimental task, subjects sat comfortably at a distance of approximately 20 cm from the typewriter. The typewriter keyboard was covered with a wooden box to avoid visual information about the hands' position. The typewriting task was performed concomitantly with EEG recording. ANOVA two-way results indicated a decreased asymmetry in sensorimotor areas in the experimental groups. Our interpretation is that moderate doses of bromazepam may improve performance on tasks with predictable elements to promote stability of psychomotor functions, but may also impair performance on tasks executed in unpredictable environments. O objetivo do estudo foi elucidar mecanismos corticais e identificar as áreas onde estas ocorrem tais mecanismos devido à interação entre bromazepam e aprendizagem motora. A amostra compreendeu 45 sujeitos hígidos distribuídos randomicamente em 3 grupos: placebo (n=15), bromazepam 3 mg (n=15) ou bromazepam 6 mg (n=15). Para a realização da tarefa experimental, sujeitos sentaram-se confortavelmente a uma distância de aproximadamente 20 cm da máquina de escrever. O teclado da máquina foi coberto com uma caixa de madeira para evitar informações visuais sobre a posição das mãos. O registro do EEGq ocorreu simultaneamente à tarefa de datilografia. Os resultados da ANOVA two-way indicaram menor assimetria em áreas sensório-motoras nos grupos experimentais. Nossa interpretação é que doses moderadas de bromazepam podem melhorar o desempenho em tarefas previsíveis por promover estabilidade das funções psicomotoras, mas pode prejudicar o desempenho em tarefas realizadas em ambientes imprevisíveis.